Éléments lithiques Hamangia des sites de Ceamurlia de Jos et Baia – Golovița (dép. de Tulcea) / Hamangia lithic elements as observed at the sites of Ceamurlia de Jos and Baia – Golovița (Tulcea County) - Manolakakis, L.; Mihail, F (Materiale și Cercetări Arheologice, 2022)
Following the recovery of the collections from D. Berciu’s excavations in Ceamurlia de Jos and Baia – Golovița, the lithic industries have been subjected to a characterization of the materials and to a technological and typological study. The exploitation focused mainly on local materials knapped on site, but the sites are also integrated into the circulation networks of semi‑finished products. The question of microlithism of Mesolithic origin is debated.